Application of geophysical methods in archaeological investigation : a case study from Lao Pako, Vientiane capital, Lao PDR - Sounthone Singsoupho (Prince of Songkla University, 2008)
Thesis (M.Sc., Geophysics)--Prince of Songkla University, 2008